2004
DOI: 10.1021/es0353255
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Mode Formation in Heavy-Duty Diesel Exhaust with and without a Particulate Filter

Abstract: Particle size distribution measurement with direct tailpipe sampling is employed to study the effect of a continuously regenerating diesel particulate filter (CRDPF) on emissions of a heavy-duty diesel engine. The CRDPF consists of an oxidation catalyst and a filter. Tests are conducted using 2 and 40 ppm sulfur content fuels and two steady-state driving modes. The formation of nucleation mode with and without CRDPF is found to depend on different parameters. Without after-treatment, size distribution is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
140
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 27 publications
14
140
2
2
Order By: Relevance
“…This data were omitted from results. In the laboratory and chase measurements the nucleation mode existence and peak diameter show great variation (Kittelson et al, 2004;Vaaraslahti et al, 2004;Rönkkö et al, 2006). The reported traffic related nucleation mode GMDs measured in roadside or traffic tunnel have a surprisingly constant values close to 20 nm.…”
Section: Characteristics Of Road-side Distributionsmentioning
confidence: 95%
See 2 more Smart Citations
“…This data were omitted from results. In the laboratory and chase measurements the nucleation mode existence and peak diameter show great variation (Kittelson et al, 2004;Vaaraslahti et al, 2004;Rönkkö et al, 2006). The reported traffic related nucleation mode GMDs measured in roadside or traffic tunnel have a surprisingly constant values close to 20 nm.…”
Section: Characteristics Of Road-side Distributionsmentioning
confidence: 95%
“…Sakurai et al (2003b) estimated a density of 0.8 g/cm 3 for these compounds. In addition, the nucleation mode formation is connected to the sulphate formation, especially when oxidation catalyst is used (Lepperhof, 2001;Maricq et al, 2002;Vaaraslahti et al, 2004). According to studies of Vogt et al(2003); Gieshaskiel et al (2005) the sulphuric acidwater nucleation seems to have an important role in the nucleation mode formation.…”
Section: Characteristics Of Road-side Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, changes in ambient temperature and gas-phase 348 T. KUHN ET AL. concentrations of these components can affect the measured particle size distributions due to evaporation or condensation. For this reason, it has been shown that the particle size distributions determined by dynamometer testing are dependent on the dilution ratios and dilution air conditions of the sampling apparatus (Holmen and Qu 2004;Lyyranen et al 2004;Vaaraslahti et al 2002). Road tunnel sampling is also subject to the unusual dilution and temperature conditions found in the tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…Former investigations on particle volatile mainly focused on the effects of fuel sulfur content, which have been well reported (Maricq et al, 2002;Vaaraslahti et al, 2004;Ristovski et al, 2006;Rönkkö et al, 2007) and induced the tightening up of diesel sulfur content. In China, the national standard of diesel fuel follows the standard EN590.…”
Section: Introductionmentioning
confidence: 99%